PENGARUH MEDIA PEMBELAJARAN BERBANTUAN APLIKASI POWTOON BERBASIS ETNOMATEMATIKA TERHADAP HASIL BELAJAR SISWA MATERI BANGUN RUANG KELAS V SD 105358 SEKIP - Apridayanti, Lisa; Siregar, Juliandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to determine the effect of learning media assisted by the Powtoon application based on ethnomathematics on student learning outcomes in the material of spatial figures in class V of SD 105358 Sekip. This study is a study with a quantitative approach using a quasi-experimental design. From the results of the study, it is known that learning media assisted by the Powtoon application based on ethnomathematics has a significant effect on the learning outcomes of class V students of SDN 105358 Sekip. This can be seen from the t-value of 5.024 and t-table 1.72. The Sig. value (2-tailed) <0.001, meaning <0.05. Because t-value> from t-table, H0 is rejected and Ha is accepted, which means that there is an effect of the use of learning media assisted by the Powtoon application based on ethnomathematics on student learning outcomes in the material of spatial figures in class V of SDN 105358 Sekip.